(untitled) (Bangladesh Journal of Infectious Diseases, 2021)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread across the world. We describe two cases of neonate, presenting with features like multisystem inflammatory syndrome (MIS-C), who presented to our neonatal unit of Dr. M R Khan Shishu Hospital, Bangladesh on August, 2020.Case 1 was a 7-day-old male infant presented at 14 hours of life with fever, poor feeding, per rectal bleeding and shock. Detailed examination revealed Down’s fancies and pallor. Case 2 was 15-day old neonate presenting with fever, rash and convulsion and his laboratory values were remarkable for high levels of C-reactive protein, D-dimer, ferritin and his Cerebrospinal fluid (CSF) findings were consistent with aseptic meningitis. Both babies were tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). First case was very critical and referred to tertiary care hospital after stabilization. 2nd case recovered completely and was discharged to home in 15 days. Though till date COVID 19 in neonate is not very well-known to us, it is essential to disseminate information among the medical community regarding severe and atypical presentations of COVID-19 in neonate as prior knowledge can help to quickly identify and treat these patients as they present in the neonatal department. Bangladesh Journal of Infectious Diseases 2020;7(2):102-106